Measuring students’ perception towards university selection: an empirical investigation on Malaysian postgraduate students - Sarwar, Abdullah Al-Mamun; Haque, A. K. M. Ahasanul; Ismail, Ahmad Zaki (International Journal of Research in Commerce & Management, 2012)
Different higher learning institutions in Malaysia offer variety of courses for the students. However, selection of the institute varied considering the different influencing factors. Thus, the purpose of this study was to examine the factors that influence the students in selecting their higher learning programs in various higher learning institutions in Malaysia. The research is based on primary data collection approach. For this purpose, a survey using self-administered questionnaires was carried out by using cluster-sampling technique. Total 300 questionnaires were distributed and 145 found to be valid for further analysis. The collected data were then analyzed and discussed by statistical techniques-descriptive statistics and ANOVA tests. It has been observed from the outcome that university teaching quality is the most important factor that influences a student in selection of his/her higher learning institution followed by university facilities, program structure and accreditation, campus facilities. This study has also found that high standard teaching influences the student interest followed by knowledgeable faculty, helpful academic staffs and knowledgeable admission staffs. This study has explored that amongst the various races in Malaysia, Malay students prefer the local universities than the other races. To end with, this study has suggested that, on perception, a proper policy may go a long way to increase the quality of teaching with the improvement of other related facilities that will help the university in attracting new students in the future.